Fiber-Shaped Triboiontronic Electrochemical Transistor - Yu, Jinran; Qin, Shanshan; Zhang, Huai; Wei, Yichen; Zhu, Xiaoxiao; Yang, Ya; Sun, Qijun (Research, 2021)
Contact electrification-activated triboelectric potential offers an efficient route to tuning the transport properties in semiconductor devices through electrolyte dielectrics, i.e., triboiontronics. Organic electrochemical transistors (OECTs) make more effective use of ion injection in the electrolyte dielectrics by changing the doping state of the semiconductor channel. However, the mainstream flexible/wearable electronics and OECT-based devices are usually modulated by electrical signals and constructed in conventional geometry, which lack direct and efficient interaction between the external environment and functional electronic devices. Here, we demonstrate a fiber-shaped triboiontronic electrochemical transistor with good electrical performances, including a current on/off ratio as high as approximate to 1286 with off-current at similar to nA level, the average threshold displacements (D-th) of 0.3 mm, the subthreshold swing corresponding to displacement (SSD) at 1.6 mm/dec, and excellent flexibility and durability. The proposed triboiontronic electrochemical transistor has great potential to be used in flexible, functional, and smart self-powered electronic textile.
CRIS-Team WoS Importer:2021-05-21